Lung cancer risk among men by occupation and industry in SYNERGY – pooled analysis of case-control studies on the joint effects of occupational carcinogens in the development of lung cancer. (19th October 2011) - Mirabelli, Dario; Merletti, Franco; Richiardi, Lorenzo; Corbin, Marine; Franch, Iván Marín; Olsson, Ann; Gustavsson, Per; Kromhout, Hans; Peters, Susan; Vermeulen, Roel; Brüske, Irene; Pesch, Beate; et al.
Abstract : Objectives: Exploratory analyses by occupation or industry are commonly conducted in case-control studies. However, cancer risks limited to certain jobs within an industry, or to a job within a given industry, become undetectable in the overall industry or job odds-ratio. Using the SYNERGY dataset we conducted an analysis based on occupations and industries combined. Methods: Data included 10 917 male cases and 13 154 male controls. Industries and jobs were coded according to ISIC Revision 2 and ISCO 1968, respectively. Odds-ratios were computed for ISCO-ISIC combinations with ≥10 study subjects, adjusting for study, age, and smoking. To allow for multiple comparisons we applied a semi-Bayes approach, shrinking towards a group mean the estimate for each ISCO-ISIC combination, previously classified as: occupation known or suspected to entail lung cancer risk, other manual workers, other non-manual workers. Results: Out of 1187 evaluated ISCO-ISIC combinations, 50 had an increased odds-ratio (p<0.05). For 26 combinations the risk remained elevated after semi-Bayes shrinkage. As an example, painters in car repair, but not in other industries like car building, had an increased risk (odds-ratio after shrinkage: 1.79, 95% CI 1.04 to 3.07). Likewise, only 8 jobs had increased risk among 63 analysed within the construction industry: miners (2.05, 1.18 to 3.55), bricklayers (1.57, 1.37 to 1.80), welders (1.57, 1.08 to 2.28), earth-moving operators (1.36, 1.05 to 1.76), carpenters (1.30, 1.08 to 1.57), other workers (1.24, 1.06 to 1.44), plumbers (1.23, 1.02 to 1.49) and labourers (1.20, 1.05 to 1.36). Conclusions: The use of ISCO-SIC combinations and a semi-Bayes approach identified specific jobs within specific industries with an increased lung cancer risk.